El juego como estrategia para el desarrollo cognitivo en los niños de 5 años - Izurieta Guzmán, María Belén (2023)
The present investigation analyzes the game as a strategy for cognitive development in 5-year-old boys and girls, with the aim of implementing a didactic guide that contains playful activities for the cognitive development of 5-year-old children from the Santiago Apóstol de Fe School. And joy. 6 activities are proposed: We are Butterflies, The ball bounces and rumbles, We are all Marines, I listen and dance, Imitate me and Socializing. The aforementioned activities are a tool of great importance for the cognitive development of the boy and girl, since, through these, knowledge, skills are acquired and above all, it gives them the opportunity to know themselves, others and the world around them. surrounds them. A mixed approach with its explanatory and descriptive correlational methods was used to understand the problem. Likewise, to validate the information, a structured questionnaire is used with its survey tool. To validate the information, an evaluation rubric for experts and users is developed. The validators considered that the guide is interesting and very useful for cognitive development and a meaningful learning process in children.